Spontaneous early-onset neurodegeneration in the brainstem and spinal cord of NSG, NOG, and NXG mice - Finesso, Giovanni; Willis, Elinor; Tarrant, James Carmine; Lanza, Matthew; Sprengers, Justin; Verrelle, Jillian; Banerjee, Esha; Hermans, Els; Assenmacher, Charles-Antoine; Radaelli, Enrico (Veterinary pathology, 2023)
The spectrum of background, incidental, and experimentally induced lesions affecting NSG and NOG mice has been the subject of intense investigation. However, comprehensive studies focusing on the spontaneous neuropathological changes of these immunocompromised strains are lacking. This work describes the development of spontaneous early-onset neurodegeneration affecting both juvenile and adult NSG, NOG, and NXG mice. The study cohort consisted of 367 NSG mice of both sexes (including 33 NSG-SGM3), 61 NOG females (including 31 NOG-EXL), and 4 NXG females. These animals were primarily used for preclinical CAR T-cell testing, generation of humanized immune system chimeras, and/or tumor xenograft transplantation. Histopathology of brain and spinal cord and immunohistochemistry (IHC) for AIF-1, GFAP, CD34, and CD45 were performed. Neurodegenerative changes were observed in 57.6% of the examined mice (affected mice age range was 6-36 weeks). The lesions were characterized by foci of vacuolation with neuronal degeneration/death and gliosis distributed throughout the brainstem and spinal cord. IHC confirmed the development of gliosis, overexpression of CD34, and a neuroinflammatory component comprised of CD45-positive monocyte-derived macrophages. Lesions were significantly more frequent and severe in NOG mice. NSG males were considerably more affected than NSG females. Increased lesion frequency and severity in older animals were also identified. These findings suggest that NSG, NOG, and NXG mice are predisposed to the early development of identical neurodegenerative changes. While the cause of these lesions is currently unclear, potential associations with the genetic mutations shared by NSG, NOG, and NXG mice as well as unidentified viral infections are considered.